KEPUTUSAN PETANI PADI DALAM MEMASARKAN PRODUKNYA DI KABUPATEN PRINGSEWU - Wulandari, Sri; Gitosaputro, Sumaryo; Adawiyah, Rabiatul (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
The research goals were to determine the factors that influence the decision of rice farmers in marketing their products, calculate the income of rice farmers in Sumberagung Village and Wargomulyo Village. This research was conductedin Sumberagung Village of Ambarawa Sub-districtand Wargomulyo Village of Pardasuka Sub-district of Pringsewu Regency. Factors that influence the decision of rice farmers in marketing their products were calculated by using ordinal logistic method, while the income was analyzed using R/C. The results showed that Factors that influence the decision of farmers in marketing their products were the price level, the amount of production, the number off amily members, the amount of family consumption, the farmer’s age, and rice cultivating experience, rice farming in Sumberagung Village was more profitable than that in Wargomulyo Village. The average income of rice farming in Sumberagung Village was around Rp12,700,372.11/ha and R/C of 1.66 while the average income on total cost of rice farming in Wargomulyo Village was around Rp7,747,238.18/ha and R/C of 1.54. Key words: decision, marketing, income